Model Based on the Integration of Agile Approaches and PMBOK Guide Practices and Its Relationship with Quality and Customer Satisfaction in WFM Telecom SAC (Innovation & Development in Engineering and Applied Science, 2026)
The study aimed to determine the relationship between a model based on the integration of agile approaches and PMBOK guide practices, and quality and customer satisfaction in WFM Telecom SAC. A quantitative, applied, descriptive correlational, and cross sectional non experimental design was used. The population and sample consisted of 31 clients selected through census sampling. Three Likert type questionnaires were applied, validated through expert judgment and with adequate reliability. The results showed a positive and significant correlation between the integrated model and quality (r = 0.682; p = 0.000), as well as between the integrated model and customer satisfaction (r = 0.802; p = 0.000). It is concluded that the articulation between agile practices and PMBOK guide practices strengthens service quality and improves customer satisfaction.
Keywords: agile approaches; PMBOK guide; quality; customer satisfaction; project management